2014
DOI: 10.1590/s0100-83582014000200018
|View full text |Cite
|
Sign up to set email alerts
|

The role of glyphosate in RR soybean production and seed quality

Abstract: -This study aimed to evaluate the production components and quality of RR soybean seeds (Roundup Ready ® ), after application of increasing rates of gliphosate. Field experiments were conducted in Mandaguari, Paraná, during two seasons. Treatments consisted of five doses of glyphosate. All applications were performed once, between development stages V 4 and V 5. The experiment was arranged in a completely randomized block design, with four replicates. Data were subjected to analysis of variance, and when signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…For the sensitive cultivar (UFV16), the small length and lack of secondary roots characterize the halt in seedling development (Cunha et al 2005). Although all cultivars showed reduction in this feature due to the increase in herbicide application rate, the greatest impact was evident in the sensitive seedlings (Albrecht et al 2014). Therefore, along with the lack of secondary roots, sudden reduction in seedling length confirmed identification of herbicide-sensitive seedlings in the germination test, as Cunha et al (2005), Pereira et al (2009a), and Bervald et al (2010) also verified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the sensitive cultivar (UFV16), the small length and lack of secondary roots characterize the halt in seedling development (Cunha et al 2005). Although all cultivars showed reduction in this feature due to the increase in herbicide application rate, the greatest impact was evident in the sensitive seedlings (Albrecht et al 2014). Therefore, along with the lack of secondary roots, sudden reduction in seedling length confirmed identification of herbicide-sensitive seedlings in the germination test, as Cunha et al (2005), Pereira et al (2009a), and Bervald et al (2010) also verified.…”
Section: Resultsmentioning
confidence: 99%
“…As the tests were conducted, reduction in the length of seedlings due to an increase in herbicide concentration was notable, especially for tolerant cultivars. When glyphosate concentration increases, physiological quality and vigor decline, even in herbicide-tolerant cultivars (Albrecht et al 2014). To confirm this reduction, the seedling length test was conducted (Pereira et al 2009b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, GR soybean is planted in 32.7 millions of hectares (Celeres, 2017). Although GR soybean is resistant to glyphosate, last years, application of glyphosate resulted in significant crop injury under certain conditions and herbicides formulations (Albrecht et al, 2014a). Recent studies have shown that glyphosate can have phytotoxic effects on soybean by affecting process as secondary metabolism, mineral nutrition, photosynthesis and biomass accumulation (Reddy et al, 2004;Zobiole et al, 2010a;Zobiole et al, 2010b;Zobiole et al, 2011;Zobiole et al, 2012).…”
Section: Introductionmentioning
confidence: 99%